Evapotranspiração e eficiência do uso da água no primeiro ciclo produtivo da figueira 'Roxo de Valinhos' submetida a cobertura morta - de Souza, Adilson Pacheco; da Silva, Andréa Carvalho; Leonel, Sarita [UNESP]; de Souza, Manoel Euzébio; Tanaka, Adriana Aki (My University, 2014)
Evaluated the evapotranspiration (ETc) and the efficiency of water use (USA) by the fig tree 'Purple Valinhos' submitted to irrigation and mulching (bagacilho of sugar cane crushed) in the first production cycle, at conditions of Botucatu, St. Paul. We used the method of soil water balance and to obtain the reference evapotranspiration method was used Montheit FAO Penman 56. For the assessment of crop coefficients (kc) we adopted the following phenological distribution: phase 1 - between transplanting and 20% of the vegetative (DV), ii) phase 2 - 20 to 80% DV, and iii) phase 3 - fruiting. Observe the cumulative ETc 409.4 and 465.8 mm in 254 days after transplanting (DAT) and averages of 1.47 and 1.67 mm day-1, with and without mulching (CC and SC). The crop coefficients (kc) mediums were 0.16, 0.43 and 0.49 for SC and 0.18, 0.44 and 0.50 for CC, in phases 1 and 3, respectively. The EUA values decrease with increasing the volume of water received and ranged between 1.65 and 3.32 kg of green figs per m3 of water for irrigated SC and CC.
Evapotranspiration and eficience of water use in first production cicle of the fig tree 'Roxo de Valinhos' under mulching
Keywords: Crop coefficients; Ficus carica; Irrigation management